2016
DOI: 10.1080/14740338.2016.1201475
|View full text |Cite
|
Sign up to set email alerts
|

An update of safety of clinically used atypical antipsychotics

Abstract: A critical issue in the treatment with atypical APs is represented by their metabolic side effect profile (e.g. weight gain, lipid and glycaemic imbalance, risk of diabetes mellitus and diabetic ketoacidosis) which may limit their use in particular clinical samples. Electrolyte imbalance, ECG abnormalities and cardiovascular adverse effects may recommend a careful baseline and periodic assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 149 publications
(174 reference statements)
2
85
0
3
Order By: Relevance
“…No safety data are so far available for children and adolescents 42. Other previous studies, systematic reviews and meta-analyses showed that iloperidone is an acceptable drug, even when compared to placebo or other antipsychotics, especially in terms of modest weight gain, no medically important changes in lipid and glucose levels and little in the way of prolactin elevation and EPS 31,39,52,63…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No safety data are so far available for children and adolescents 42. Other previous studies, systematic reviews and meta-analyses showed that iloperidone is an acceptable drug, even when compared to placebo or other antipsychotics, especially in terms of modest weight gain, no medically important changes in lipid and glucose levels and little in the way of prolactin elevation and EPS 31,39,52,63…”
Section: Resultsmentioning
confidence: 99%
“…This pharmacodynamic profile with low affinity to H1 and M1 receptors would lead to minimal sedation, cognitive impairment and mild weight gain. The extremely low binding at cholinergic receptors suggests a low risk of anticholinergic symptoms (eg, blurred vision and dry mouth), as well as a lower EPS liability 42,43…”
Section: Resultsmentioning
confidence: 99%
“…Substantial consensus exists about the pharmacological signature of lurasidone hydrochloride across sources assessing either preclinical or clinical studies on the matter [6064], as briefly synthesized below.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, its lack of affinity for some receptors (e.g., histamine H1, acetylcholine M1) would predict improved (metabolic and cognitive) tolerability with respect to alternative SGAs options approved by the FDA for BD in adults [61, 63]. Favorable D2/5-HT2A balance would predict lower propensity for extrapyramidal symptoms [64]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation